Targeting ACAT1 in cancer: from threat to treatment - Sun, Tie; Xiao, Xuan (Frontiers in Oncology, 2024)
Altered cholesterol metabolism has been identified as a critical feature of cancers. Cholesterol functions as the main component of cell membrane, cholesterol and is required for sustaining membrane integrity and mediating signaling transduction for cell survival. The intracellular level of cholesterol is dynamically regulated. Excessive cholesterol could be converted to less toxic cholesteryl esters by acyl-coenzyme A:cholesterol acyltransferases (ACATs). While ACAT2 has limited value in cancers, ACAT1 has been found to be widely participated in tumor initiation and progression. Moreover, due to the important role of cholesterol metabolism in immune function, ACAT1 is also essential for regulating anti-tumor immunity. ACAT1 inhibition may be exploited as a potential strategy to enhance the anti-tumor immunity and eliminate tumors. Herein, a comprehensive understanding of the role of ACAT1 in tumor development and anti-tumor immunity may provide new insights for anti-tumor strategies.